Response of hard wheat (Marjawii Cultivar) to seeding rates under El – Baida conditions at Al-Jabal Al-akhdar- Libya (Albayan Scientific Journal, 2023)
Two field experiments were conducted at the Crops science Research Station at Agronomy Department –Agriculture Faculty at Omar Al-Mukhtar University investigated the  effect of seeding dates (First Dec, Mid Dec and First Jan) on growth and yield traits during the two seasons 2015-2016 and 2016-2017. The results exhibited significant increase of crop growth rate; bearing tillers m-2, spike weight, number of spike grains and weight from 1st Dec regarding to 1st Jan. Mid Dec gave largest leaf area index and plant height, comparing to 1stJan in both two seasons. Significant increase of biological yield 5.95, 5.86 tha-1; grain yield 1.26, 1.26 tha-1 and straw yield 4.69, 4.60 tha-1 from 1st Dec seeding comparing to the least 2.54, 2.56, 0.49, 0.70 and 2.05, 1.86 tha-1from biological, grain and straw yield, respectively during 1st Jan seeding meanwhile that date recorded significant increase in second season only in harvest index and grains protein contents 12.66, 12.68% comparing to 10.84, 10.86% during 1st Dec seeding in both two Seasons, respectively. Incoelusion seeding at 1st Dec gave the greatest quantity, while 1st Jan gave greatest quality
Keywords: Hard Wheat (Marjawii cultivar); Seeding dates